2020
DOI: 10.1108/ajim-03-2020-0067
|View full text |Cite
|
Sign up to set email alerts
|

Data privacy-related behavior and concerns of activity tracking technology users from Germany and the USA

Abstract: PurposeThis investigation aims to examine the differences and similarities between activity tracking technology users from two regions (the USA and Germany) in their intended privacy-related behavior. The focus lies on data handling after hypothetical discontinuance of use, data protection and privacy policy seeking, and privacy concerns.Design/methodology/approachThe data was collected through an online survey in 2019. In order to identify significant differences between participants from Germany and the USA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The data privacy concerns (DPCs) are so eminent that they have led to specific regulations (e.g., in the United States, Data Accountability and Trust Act of 2009). A recent study on activity tracing applications has established that consumers have considerable importance to data privacy and the resulting usage behavior (Ilhan & Fietkiewicz, 2020). The foregone discussion reinforces the argument that DPCs are vital in adopting CTA.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…The data privacy concerns (DPCs) are so eminent that they have led to specific regulations (e.g., in the United States, Data Accountability and Trust Act of 2009). A recent study on activity tracing applications has established that consumers have considerable importance to data privacy and the resulting usage behavior (Ilhan & Fietkiewicz, 2020). The foregone discussion reinforces the argument that DPCs are vital in adopting CTA.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…A survey with the goal to investigate the likeness and dissimilarities of fitness trackers users’ privacy attitudes from USA and Germany showed that the weight of a number of user privacy concerns varied considerably between the two groups (Ilhan and Fietkiewicz 2020 ). The introduction of the GDPR in the EU was the driving force for this study, and it has been shown that the European users are using their GDPR rights and have become more responsible of their data.…”
Section: Introductionmentioning
confidence: 99%
“…( 2018 ) A questionnaire where exploratory factor analysis is applied to investigate if there is a relationship between the intention of fitness tracker users to disclose personal data and to continue using the wearable device Users are more likely to continue using a fitness tracker if the anticipated benefits are surpassing their privacy concerns Third-party access to personal data, data used for other purposes than stated, devices collecting too much information, activity monitoring Fietkiewicz and Ilhan ( 2020 ) An online survey from EU and USA participants who are current, former or non-users of fitness tracking applications to determine their awareness of data collection and their privacy concerns Users who normally feel insecure about their online data privacy are also more likely to be concerned about the protection of the privacy of their data collected from fitness trackers Third-party access to personal data, profiling Zimmer et al. ( 2020 ) A survey and semi-structured interviews with fitness trackers users to determine the pros and cons that users notice from their interaction with their devices Users have low levels of privacy concerns, they find that the benefits of using a fitness tracker exceed any disadvantages, they do not perceive data collected from fitness trackers as sensitive and they are not aware of possible privacy threats Third-party access to personal data, third parties can use my data against me Ilhan and Fietkiewicz ( 2020 ) A survey on USA and Germany fitness trackers users to investigate the differences between the users’ privacy attitudes after the GDPR application in the EU EU users are more responsible of their data Third-party access to personal data, third parties can use my data against me, profiling Velykoivanenko et al. ( 2021 ) A longitudinal study, an online survey and interviews with fitness trackers users to comprehend how they perceive the privacy inference risks of these devices The participants are apprehensive of the types of information that might be inferred about them Third parties can use my data against me, damage to interpersonal relationships, inferring various types of information …”
Section: Introductionmentioning
confidence: 99%
“… Contextually, it should be noted that users in German‐speaking Europe generally expect significantly more damage and attribute higher probability to privacy‐related violations than, e.g., U.S. users (Ilhan & Fietkiewicz, 2021). …”
mentioning
confidence: 99%